2014
DOI: 10.4049/jimmunol.1401541
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmacytoid Dendritic Cell as the Swiss Army Knife of the Immune System: Molecular Regulation of Its Multifaceted Functions

Abstract: Plasmacytoid dendritic cells (pDC) have been regarded as the “professional type I interferon producing cells” of the immune system following viral recognition that relies on the expression of Toll-like receptor (TLR)7 and TLR9. Furthermore, pDC link the innate and adaptive immune systems via cytokine production and antigen presentation. More recently their ability to induce tolerance and cytotoxicity has been added to their “immune skills”. Such broad range of actions, resembling the diverse functional feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 117 publications
2
31
0
Order By: Relevance
“…4A). These depletion experiments confirmed that pDCs from HIV-infected donors are the primary source of IFN-α induced by GS-9620, similar to what was previously reported for other TLR7 agonists in cells from healthy donors (35). …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…4A). These depletion experiments confirmed that pDCs from HIV-infected donors are the primary source of IFN-α induced by GS-9620, similar to what was previously reported for other TLR7 agonists in cells from healthy donors (35). …”
Section: Resultssupporting
confidence: 89%
“…pDCs are a key part of the innate immune system that responds to viral nucleic acids by producing type I IFN and other stimulatory cytokines (35). Upon stimulation, pDCs can devote up to 60% of their transcriptome to expressing type I and type III IFNs (47).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the two principal lineages of dendritic cells, pDCs diverge from conventional DCs (cDCs) during maturation in the bone marrow and are recognized mainly for their rapid and massive production of type I IFN (IFNα/β) in response to viral infection (2). Although generally viewed as weak antigen-presenting cells by comparison with cDCs, pDCs interact with many types of cells, such as NK cells, cDCs, T cells, and B cells through their secretion of cytokines and chemokines in addition to type I IFN, as well as through their expression of various costimulatory molecules (3,4). Thus, pDCs are capable of activating CD4 + helper and regulatory T cells and CD8 + cytotoxic T cells (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Indeed, the primary host defense carried out by innate immune cells is often a central target for subversive efforts by both small RNA and larger DNA viruses. This is highlighted by the fact that IFNs and IFN-producing innate cells are frequently counterattacked by different and diverse virus types, being pivotal to the interplay of innate and adaptive responses in immunity [29][30][31].…”
Section: Viral Evasion Of Ifn Responsesmentioning
confidence: 99%